2009
DOI: 10.1002/crat.200900167
|View full text |Cite
|
Sign up to set email alerts
|

Sintering behavior of ZnO:Al ceramics fabricated by sol‐gel derived nanocrystalline powders

Abstract: ZnO:Al ceramics (Zn:Al, 0.95:0.05) were prepared by using sol-gel derived nanocrystalline powders. XRD patterns of the doped ceramics revealed the existence of both zincite (JCPDS 36-1451) and gahnite (JCPDS 5-0669) phases. Gahnite phase (ZnAl 2 O 4 ) was segregated along the ZnO grain boundaries. At the sintering temperature of 1200 °C, relative density of the undoped and Al doped ceramics were measured as 0.695 and 0.628, respectively. Both grain size and relative density of the ceramics decreased with Al do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…Based on Han's results, the kinetic exponent ( n ) of pristine ZnO and AZO is taken as 3 and 4, respectively . The grain growth activation energy of pristine ZnO ceramic is estimated to be 169 ± 18 kJ/mol, which is closer to the reported value of 200 kJ/mol . Higher grain growth activation energy is observed in the case of AZO, i.e., 374 ± 36 kJ/mol.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Based on Han's results, the kinetic exponent ( n ) of pristine ZnO and AZO is taken as 3 and 4, respectively . The grain growth activation energy of pristine ZnO ceramic is estimated to be 169 ± 18 kJ/mol, which is closer to the reported value of 200 kJ/mol . Higher grain growth activation energy is observed in the case of AZO, i.e., 374 ± 36 kJ/mol.…”
Section: Resultsmentioning
confidence: 55%
“…adopted the TSS method for pristine ZnO and reported a density of 98% with grain size on the order of less than 1 μm. Similarly, other investigators have reported various methods for sintering nanocrystalline or fine‐grained ZnO powder and ceramics . However, the effect of the TSS method on the distribution of dopants in multi‐component ceramics remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…And there are some small ZnO diffraction peaks (JCPDS card No. 36–1451) [18] observed indicating that the final products of ZnS: Er 3+ /Yb 3+ powders coexisted little ZnO.…”
Section: Resultsmentioning
confidence: 99%
“…Among the above methods to prepare ZnO, wet chemical synthesis such as sol-gel [20,21] and precipitation method [22,23] have the merits of uniform particle distribution as well as lower processing temperature, but induce impurities in the particles from starting materials and metal ions having a different melting temperature. In comparison with other oxide preparation techniques the combustion method is a low temperature synthesis route, which can produce a more uniform particle distribution.…”
Section: Introductionmentioning
confidence: 99%